1997
DOI: 10.1111/j.1346-8138.1997.tb02316.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Hidroacanthoma Simplex

Abstract: There are many conditions characterized by nests of cells within the epidermis. One of them, hidroacanthoma simplex, has been regarded as an epidermal tumor differentiating to intraepidermal eccrine duct cell. We report a case of hidroacanthoma simplex with the results of immunohistochemical study. Staining for 35 beta H11 (reacting with keratin No. 8), 35 beta E12 (reacting with keratin No. 1, 5, 10, 11), S-100 protein, and CEA was negative in the tumor cell nests; these monoclonal antibodies stained the nest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A previous immunohistochemical study 11 of cytokeratins in HS showed a negative reaction for 35 β H11 (CK8) and 35 β E12 (CK1, 5, 10 and 11). Our study clearly showed the presence in HS of CK14 and 17, and the absence in HS of CK1, 10 and 19.…”
Section: Cytokeratin Expression In the Acrosyringium Intradermal Ducmentioning
confidence: 80%
“…A previous immunohistochemical study 11 of cytokeratins in HS showed a negative reaction for 35 β H11 (CK8) and 35 β E12 (CK1, 5, 10 and 11). Our study clearly showed the presence in HS of CK14 and 17, and the absence in HS of CK1, 10 and 19.…”
Section: Cytokeratin Expression In the Acrosyringium Intradermal Ducmentioning
confidence: 80%
“…Hidroacanthoma simplex is a rare skin tumor described as verrucous keratotic plaque clinically resembling seborrheic keratosis or Bowen's disease. 11,12 The tumor often occurs on lower extremities and trunk of elderly persons. In our study, all three cases also arose on extremities, which was compatible with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining with carcinoembryonic antigen, epithelial membrane antigen and antikeratin antibodies seems to be not helpful in diagnosing HS [5]. However, some interesting variety of findings on immunostaining with antikeratin antibodies has been reported [5][6][7]. Electron microscopy has been reported to be helpful in diagnosing HS [5].…”
mentioning
confidence: 99%